Phytochemical study of South American Ilex - Guillaume, D.; Gosmanni, G.; Schenkel, E.P. Schenkel (Malaysian Journal of Science, 2000)
The structure of five triterpenoid saponins (matesaponins 1-5) isolated from Ilex paraguariensis is reported. Structural elucidation was performed using mass spectrometry and NMR techniques. ABSTRAK Struktur 5 saponina triterpenoid dari Ilex paraguariensis dilaporkan. Elusidasi struktur dijayakan dengan menggunakan kaedah RMN dan kaedah spektrometri jisim. (Ilex paraguariensis, Aquifoliaceae, matesaponin, mate)